Comparison between microwave and conventional sintering on the properties and microstructural evolution of tetragonal zirconia - Ramesh, Singh; Zulkifli, Nurin Wahidah Mohd; Tan, Chou Yong; Wong, Yew Hoong; Tarlochan, Faris; Ramesh, Subramaniam; Teng, W.D.; Sopyan, Iis; Bang, Le Thi; Sarhan, Ahmed Aly Diaa Mohammed (Elsevier, 2018)
In this research, the comparison between microwave sintering and conventional sintering on the mechanical properties and microstructural evolution of 3 mol% yttria-stabilised zirconia were studied. Green bodies were compacted and sintered at various temperatures ranging from 1200 °C to 1500 °C. The results showed that microwave assisted sintering was beneficial in enhancing the densification and mechanical properties of zirconia, particularly when sintered at 1200 °C. It was revealed that as the sintering temperature was increased to 1400 °C and beyond, the grain size and mechanical properties for both microwave- and conventional-sintered ceramics were comparable thus suggesting that the sintering temperature where densification mechanism was activated, grain size was strongly influenced by the sintering temperature and not the sintering mode.